'It's not magic': A qualitative analysis of geriatric physicians' explanations of cardio‐pulmonary resuscitation in hospital admissions - Anca‐Cristina Sterie; Laura Jones; Ralf J. Jox; Eve Rubli Truchard (Wiley, 2021)
Abstract Background Discussing patient preferences for cardio‐pulmonary resuscitation (CPR) is routine in hospital admission for older people. The way the conversation is conducted plays an important role for patient comprehension and the ethics of decision making. Objective The objective was to examine how CPR is explained in geriatric rehabilitation hospital admission interviews, focussing on circumstances in which physicians explain CPR and the content of these explanations. Method We recorded forty‐three physician‐patient admission interviews taking place in a hospital in French‐speaking Switzerland, during which CPR was discussed. Data were analysed in French with thematic and conversation analysis, and the extracts used for publication were translated into English. Results Mean patient age was 83.7 years; 53.5% were admitted for rehabilitation after surgery or traumatism. CPR was explained in 53.8% of the conversations. Most explanations were brief and concerned the technical procedures, mentioning only rarely potential outcome. With one exception, medical indication and prognosis of CPR did not feature in these explanations. Explanations occurred either before the patient's answer (as part of the question about CPR preferences) or after the patient's answer, generated by patients' indecision, misunderstanding and by the need to clarify answers. Discussion and conclusions The scarcity and simplicity of CPR explanations highlight a reluctance to have in‐depth discussions and reflect the assumption that CPR does not need explaining. Providing patients with accurate information about the outcomes and risks of CPR is incremental for reaching informed decisions and patient‐centred care. Patient contribution Patients were involved in the data collection stage of the study.